2009
DOI: 10.1021/jm900298c
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A2A Receptor-Antagonist/Dopamine D2 Receptor-Agonist Bivalent Ligands as Pharmacological Tools to Detect A2A-D2 Receptor Heteromers

Abstract: Adenosine A(2A) (A(2A)R) and dopamine D(2) (D(2)R) receptors mediate the antagonism between adenosinergic and dopaminergic transmission in striatopallidal GABAergic neurons and are pharmacological targets for the treatment of Parkinson's disease. Here, a family of heterobivalent ligands containing a D(2)R agonist and an A(2A)R antagonist linked through a spacer of variable size was designed and synthesized to study A(2A)R-D(2)R heteromers. Bivalent ligands with shorter linkers bound to D(2)R or A(2A)R with hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
123
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(126 citation statements)
references
References 55 publications
1
123
0
2
Order By: Relevance
“…Examples of this approach are found in the work of Whistler, Franco and colleagues. The Whistler group showed that the agonist 6Ј-guanidinoaltrindole (6Ј-GNTI) selectively activates the heterodimer of -and -opioid receptors to produce an analgesic response in mice (Waldhoer et al, 2005), and the Franco group designed hetero-bivalent ligands containing both a D 2 R agonist and an A 2A R antagonists coupled by chemical spacer to target the A 2A R-D 2 R hetrodimer as a new strategy for the treatment of Parkinson's disease (Soriano et al, 2009). …”
Section: Perspectives and Conclusionmentioning
confidence: 99%
“…Examples of this approach are found in the work of Whistler, Franco and colleagues. The Whistler group showed that the agonist 6Ј-guanidinoaltrindole (6Ј-GNTI) selectively activates the heterodimer of -and -opioid receptors to produce an analgesic response in mice (Waldhoer et al, 2005), and the Franco group designed hetero-bivalent ligands containing both a D 2 R agonist and an A 2A R antagonists coupled by chemical spacer to target the A 2A R-D 2 R hetrodimer as a new strategy for the treatment of Parkinson's disease (Soriano et al, 2009). …”
Section: Perspectives and Conclusionmentioning
confidence: 99%
“…Although the functional significance and consequences of a number of such pairings, including those between dopamine D 1 and D 2 (10 -12) and -and ␦-opioid (13-16) receptor subtypes, have been explored, the relevance of other pairings has been studied less extensively. With notable exceptions such as interactions between adenosine and dopamine receptor subtypes (17,18), this is particularly true of pairings between GPCRs for which the endogenous agonist ligands are distinct. Despite this, a number of commentators have discussed the potential for such heteromers to respond to ligands in unique ways and to offer the potential as novel sets of drug targets (3, 19 -22).…”
mentioning
confidence: 99%
“…The merging of pharmacophores for an agonist at one receptor (D 2 ) and an antagonist at another receptor (A 2A ) is difficult or even impossible. Therefore all published approaches have connected two pharmacophores, one for each receptor, by linkers of different length (Dalpiaz et al 2012;Jorg et al 2015;Soriano et al 2009). Compound 27 is a dopamine prodrug which releases dopamine after amide hydrolysis (Fig.…”
Section: Dual a 2a Antagonists And Dopamine Agonistsmentioning
confidence: 99%